Dating Violence and Homicide with Younger Adults: Are We Taking the Dangers Seriously Enough? - Qureshi, Corinne (2019)
A significant proportion of domestic violence involves dating partners, however little research has examined domestic homicides in this context. The purpose of the current study was to examine domestic homicides in the context of dating violence in comparison to cohabiting and married couples. The dataset for these comparisons was derived from the Ontario Domestic Violence Death Review Committee (DVDRC). The study hypothesized that dating partners would differ from their cohabiting and married counterparts in several areas due to the unique nature of dating relationships, whereby they are less likely to be characterized by legal, economic, and familial ties to their partner. Specifically, victims’ involvement with police, help seeking behaviour, and formal interventions were expected to be less prevalent among dating partners. The study yielded mixed results, whereby victims' system involvement was generally low across relationship types. Significant differences emerged within age and relationship type, indicated by comparisons of cases that had victim-specific police contact and formal interventions documented. Implications for intervention and suggestions for future research are discussed